Tipong pinoy : Philippine drama. (Sl : NCAA / Felta)
A television program on the Philippine Drama - its origin, the contemporary drama and contemporary musical drama. Icludes feature on Senakulo, Komedya and Sarswela, and the Community theatre Barasoain Kalinangan Foundation.
Keywords: Philippine drama; Drama; Tipong pinoy